KEBERLANJUTAN PERIKANAN TANGKAP DI KOTA TERNATE PADA DIMENSI EKOLOGI - Rommy M. Abdullah; Sugeng Hari Wisudo; Daniel R. Monintja; M. Fedi A. Sondita (Buletin PSP, 2011)
The objective of this study is to determine sustainability status of fisheries captures at Ternate city bases on ecology dimension using RAPFISH approach. RAPFISH (Rapid Appraissal for Fisheries) approach, that is a technique ordination multi-discipline and non-parametric that used to evaluate and determine the fisheries status, in the case of sustainability. This research indicates that in general sustainability index fishery captures in Ternate city exists from criterion 51-75 (fair sustainable status). Fishing gear of hand line has index value highest sustainability (72,58%), whereas index lowest sustainability is fishing gear of tuna long line (54,01%). Simulation Result Monte Carlo indicates that spreading of index plots sustainability it is at distance that not far and each other nearest with position of sustainability status ordination until support determination appropriate of sustainability status ordination analyzed. Sensitivity Analysis shows that attribute migratory range, range collapse, and catch pra-matuary are attribute that very high effect on value of sustainability fisheries captures index at ecology dimension in Ternate City.